Disturbance control in flexible manufacturing - Kuivanen, R.
This article proposes that feedback from disturbances be used to redefine the system to overcome unwanted disturbances. This article describes the typical features of flexible manufacturing systems (FMS). A model and a classification is presented that explains the different orientations to disturbances and causes of disturbances based on a case study FMS in Finland.
Keywords: Flexible manufacturing systems (FMS).; Disturbances